2002
DOI: 10.1046/j.1365-8711.2002.05231.x
|View full text |Cite
|
Sign up to set email alerts
|

Shocks, illumination cones and intrinsic gas structures in the extreme radio galaxy 3C 265

Abstract: We present deep, narrow‐band and continuum images of the powerful high‐redshift radio galaxy 3C 265 (z=0.811), taken with the TAURUS Tunable Filter on the William Herschel Telescope, together with detailed long‐slit spectroscopic observations along the axis defined by the UV/optical emission elongation. The deep images reveal the existence of cones in the ionization structure of 3C 265 within ∼7 arcsec (58 kpc) of the nucleus, where the emission‐line structure is not observed to be closely aligned with the rad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 42 publications
(81 reference statements)
5
23
0
Order By: Relevance
“…5). Off-axis gas not aligned with the radio jet axis and out to a galactocentric radius of 65 kpc in the radio galaxy 3C 265 at z = 0.8 may indeed be powered by shocks, perhaps with additional photoionization from soft X-ray emission from the precursor of the shock (Solórzano-Iñarrea et al 2002). However, as argued by Le Tiran et al (2011) and Nesvadba et al (2006), it is difficult to reach high Hα surface brightnesses as observed with shocks.…”
Section: Line Diagnosticsmentioning
confidence: 92%
“…5). Off-axis gas not aligned with the radio jet axis and out to a galactocentric radius of 65 kpc in the radio galaxy 3C 265 at z = 0.8 may indeed be powered by shocks, perhaps with additional photoionization from soft X-ray emission from the precursor of the shock (Solórzano-Iñarrea et al 2002). However, as argued by Le Tiran et al (2011) and Nesvadba et al (2006), it is difficult to reach high Hα surface brightnesses as observed with shocks.…”
Section: Line Diagnosticsmentioning
confidence: 92%
“…It has an extreme emission‐line luminosity (McCarthy 1988), which makes 3C 265 ideal for the study of emission‐line properties in distant radio galaxies. Its continuum structure extends over more than 10 arcsec and [O ii ]λ3727 images show emission over more than 30 arcsec (Rigler et al 1992; McCarthy, Spinrad & van Breugel 1995; Solórzano‐Iñarrea et al 2002). HST images reveal the bizarre optical morphology of this object, with the nucleus surrounded (in projection) by emission regions or companion galaxies (Longair, Best & Rottgering 1995).…”
Section: Previous Observationsmentioning
confidence: 99%
“…The ionization of these EELR is thought to be due to a combination of photoionization by the central AGN and shocks induced by interactions with the radio source, with AGN photoionization dominating near the nucleus, and jet–cloud interactions becoming more important at larger radii (e.g. Solórzano‐Iñarrea, Tadhunter & Bland‐Hawthorn 2002). By investigating the properties of these EELR we can learn about the interactions between the radio source and its environment.…”
Section: Introductionmentioning
confidence: 99%
“…Baum & Heckman ; Tadhunter et al ) is whether these EELR are ionized by photons from the nucleus or by shocks driven by the jets; in the most powerful radio sources, normally found at high redshift, there is often evidence that the optical emission‐line material is either ionized or at least strongly affected by jet‐driven shocks, which requires a direct interaction between the jets and the warm/cold ( T < 10 4 K) phase of the interstellar medium (ISM) of the host galaxy (e.g. Sólorzano‐Iñarrea, Tadhunter & Bland‐Hawthorn ; Nesvadba et al ).…”
Section: Introductionmentioning
confidence: 99%